Stabilisation of Pathologic Proximal Femoral Fracture near the Growth Plate with Use of a Locking Plate and Transphyseal Screws - Roman Michalik; Frank Hildebrand; Heide Delbrück (MDPI AG, 2022)
Aneurysmal bone cyst (ABC) is a benign osseus lesion with a high pathologic fracture risk. The described treatment options are varied and inconsistent. For successful treatment results, it is essential to prevent recurrence and sufficiently stabilise the weakened bone. Lesions close to the growth plates, especially in the femoral neck region, are challenging to stabilise in children. In this study, 27 clinics, including 11 sarcoma centres, 15 paediatric orthopaedic clinics, and one sarcoma/paediatric orthopaedic centre, were surveyed and asked about their treatment approaches for an exemplary case of ABC in the femoral neck causing a pathological fracture in a 20-month-old infant, with a response rate of 81%. The heterogeneity of treatment options described in the literature is consistent with the survey results. The most favoured approach was curettage, defect filling of any kind, and surgical stabilisation. However, the lesion stabilisation option introduced in this paper, which involves the use of transphyseal screws, was not mentioned in the survey and has not been reported in the literature. Contrary to the existing concepts, our technique offers high stability without significant growth restriction. Transphyseal screws are also suitable for the treatment of femoral neck fractures of other aetiologies in children.